2020
DOI: 10.1136/thoraxjnl-2019-213936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on asthma control in patients with vitamin D deficiency: the ACVID randomised clinical trial

Abstract: BackgroundThe relationship between asthma and vitamin D deficiency has been known for some time. However, interventional studies conducted in this regard have shown conflicting results.ObjectiveTo evaluate the efficacy of vitamin D supplementation in asthmatic patients in improving the degree of control of asthma.MethodsRandomised, triple-blind, placebo-controlled, parallel-group study in adult asthmatic patients with serum 25-hydroxyvitamin-D3 <30 ng/mL. The intervention group received oral supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…In a study by Andujar-Espinosa et al, majority of the patients (78%) were women. 19 The most common age group to be affected is the paediatric age group followed by the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Andujar-Espinosa et al, majority of the patients (78%) were women. 19 The most common age group to be affected is the paediatric age group followed by the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D supplementation may reduce skin inflammation in subsets of atopic dermatitis patients who have recurrent bacterial infection and pre-existing vitamin D deficiency, however further placebo-controlled randomised control trials are needed to confirm these effects in other cohorts ( 276 ). A randomised clinical trial found that patients with asthma and vitamin D deficiency had significantly improved asthma control after 6 months of weekly oral calcifediol (1,25 dihydroxy vitamin D3) supplementation compared to placebo ( 277 ). Indeed, long-term supplementation with vitamin D may also be protective against inflammatory disease.…”
Section: Utilising Dietary Therapy In the Treatment Of Human Gastroin...mentioning
confidence: 99%
“…The ACVID clinical trial [45], which was published in 2020, included 112 asthmatic patients with 25(OH)D deficiency and was based on a short follow-up period of six months. The authors administered calcifediol to treat 25(OH)D deficiency.…”
Section: Vitamin D Deficiency and Asthmamentioning
confidence: 99%
“…Furthermore, calcifediol does not require hepatic 25-hydroxylation. Functional impairment of CYP2R1 activity has been reported in patients with obesity, malabsorption [160] or inflammatory lung diseases such as COPD or asthma [45,59].…”
Section: Vitamin D and Other Respiratory Diseasesmentioning
confidence: 99%